Peran Komisaris Independen dalam Memoderasi Thin Capitalization, Financial Distress dan Kepemilikan Asing Terhadap Agresivitas Pajak - Ni Gusti Ayu Nila Suciadnyani; Nyoman Ari Surya Darmawan; I Gusti Ayu Purnamawati (Politeknik Ganesha Medan, 2025)
Tax aggressiveness is an important issue that is often associated with companies' efforts to minimize tax burdens through certain strategies. Especially in the context of multinational companies. This study aims to provide empirical evidence on the effect of thin capitalization, financial distress and foreign ownership on tax aggressiveness, with independent commissioners as a moderating variable. This study uses a quantitative approach with panel data regression analysis on multinational companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. With a purposive sampling technique, a total of 96 sample companies were obtained in the observation period which were analyzed using STATA software. The results of the study show that thin capitalization and foreign ownership have no effect on tax aggressiveness. While financial distress has a negative effect on tax aggressiveness. In addition, independent commissioners are unable to moderate the effect of thin capitalization, financial distress and foreign ownership on tax aggressiveness. This study provides a new understanding that tax aggressiveness decisions are more influenced by internal conditions such as financial distress and the effectiveness of internal supervision than by external pressures. This has an impact on the need for improvements in corporate governance, especially strengthening the role of independent commissioners and aligning financial strategies and tax policies to comply with the principles of compliance and transparency.